1995
DOI: 10.1007/bf02111871
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica endocarditis: Case report and literature review

Abstract: Endocarditis is a rare manifestation of Yersinia enterocolitica infection. The case of a 45-year-old man who presented with high fever and in whom prosthetic valve Yersinia enterocolitica endocarditis was diagnosed is described. The patient was successfully treated with ceftriaxone plus tobramycin, as proved by negative cultures of the prosthesis removed at the end of therapy. Including the patient reported, only 12 cases of Yersinia enterocolitica endocarditis have been published to date, two of which describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Treatment of extraintestinal disease or complications should be based on results of susceptibility testing of a given isolation in vitro. Most of the published studies report that endocarditis due to Y. enterocolitica was treated with 脽-lactams and/or aminoglycosides [9,10]. Our patient was successfully treated with a combination of an aminoglycoside (netilmicin) and a quinolone (ofloxacin).…”
Section: Discussionmentioning
confidence: 75%
“…Treatment of extraintestinal disease or complications should be based on results of susceptibility testing of a given isolation in vitro. Most of the published studies report that endocarditis due to Y. enterocolitica was treated with 脽-lactams and/or aminoglycosides [9,10]. Our patient was successfully treated with a combination of an aminoglycoside (netilmicin) and a quinolone (ofloxacin).…”
Section: Discussionmentioning
confidence: 75%
“…Yersinia enterocolitica, a member of the Enterobacteriaceae, causes bacteremia and septicemia that are usually associated with a predisposing underlying disease such as an iron-overloading state (hemoglobin disease, chronic hemolytic anemia, hemochromatosis, acute iron poisoning, deferoxamine therapy, alcoholism, and cirrhosis), immunosuppressive therapy, and immunocompromise such as that due to HIV infection. Twelve cases of Y. enterocolitica endocarditis have been reported in the literature, including two prostheticvalve infections (101). The involved serotypes were O:3, O:8, and O:9, which are termed virulent serotypes and represent the most frequent causes of sporadic human disease (101).…”
Section: Gram-negative Bacillimentioning
confidence: 99%
“…Twelve cases of Y. enterocolitica endocarditis have been reported in the literature, including two prostheticvalve infections (101). The involved serotypes were O:3, O:8, and O:9, which are termed virulent serotypes and represent the most frequent causes of sporadic human disease (101). Rheumatic heart disease was reported in three patients.…”
Section: Gram-negative Bacillimentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mycotic aneurysms due to Y. enterocolitica requiring successive operations in the same patient have been described (Donald et al, 1996). Endocarditis is also recognized (Appelbaum et al, 1983;Giamarellou et al, 1995) and has now been reported from a total of 12 patients in the literature (Brouqui and Raoult, 2001), with no obvious serotype association.…”
Section: Clinical Manifestations Of Y Enterocolitica Infections (Mikmentioning
confidence: 88%